Constructing enterprise input-output tables: A case study of New Zealand dairy products - Manfred Lenzen; Sven Lundie (Journal of Economic Structures, 2012)
We describe an efficient method for estimating enterprise input-output tables for cases when only information on marginal totals is available. In order to estimate the production structure of enterprises, we utilize engineering knowledge to construct a qualitative prior containing 1 wherever an output may require an input, and 0 otherwise. This qualitative prior is then scaled by the total enterprise turnover, and subsequently reconciled using the RAS method in order to meet accounting rules. We demonstrate the usefulness of this method in an application to dairy product manufacturing in New Zealand, where we estimate the input-output tables for 22 production sites. Our analysis is carried out in units of mass, and hence the accounting rules are mass balance requirements.
Keywords: Q56; C65; L66; 330; enterprise input-output tables; RAS matrix balancing; qualitative prior; dairy industry